Optimization of Moringa Leaf (Moringa Oleifera Lamk) Ethanol Extract with Span 80 and Tween 80 Emulsifier - Diyah Ayu Wulandari; Nurul Izzati Osman; Tatina Siska Wardani; Muladi Putra Mahardika (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Moringa plant (Moringa Oleifera Lamk) contains various free radical inhibitory molecules, such as phenolic compounds (phenolic acids, flavonoids, quinones, coumarins, lignans, stilbenes, tannins), nitrogen compounds (alkaloids, amines, betalains), vitamins, terpenoids (including carotenoids) and several other endogenous metabolites rich in antioxidant activity. When span 80 and tween 80 are mixed in a suitable composition and in their manufacture the aqueous phase is dispersed into the oil, span 80 and tween 80 will be arranged alternately at the interface of the oil phase and water phase forming a monolayer that surrounds the droplets so as to produce good emulsifying properties. and form a stable O/A type emulsion. Determine the optimum concentration of span 80 and tween 80 in the formulation of ethanol extract cream of Moringa leaves (Moringa oleifera Lamk) by testing the physical properties and cream of the cream In this study, concentration variations of span 80 and tween 80 to see the best physical properties. The statistical analysis using the Simplex Lattice Design versi 11 method with the parameters of adhesion, dispersion, pH, viscosity, and protective power. The optimum formula is in formula 2 with a ratio of span 80: tween 80 is 0:1 which indicates a desirability value of 0.986. Conclusions. The optimum formula is formula 2 with a ratio of span 80 and tween 80 0:1, where the results of the stability test by cycling test have relatively better physical stability in terms of organoleptic, homogeneity, disperersion, adhesion, pH, viscosity.